2013
DOI: 10.1093/hmg/ddt069
|View full text |Cite
|
Sign up to set email alerts
|

Tumoral EPAS1 (HIF2A) mutations explain sporadic pheochromocytoma and paraganglioma in the absence of erythrocytosis

Abstract: Pheochromocytomas (PCCs) and paragangliomas (PGLs) are chromaffin-cell tumors that arise from the adrenal medulla and extra-adrenal paraganglia, respectively. The dysfunction of genes involved in the cellular response to hypoxia, such as VHL, EGL nine homolog 1, and the succinate dehydrogenase (SDH) genes, leads to a direct abrogation of hypoxia inducible factor (HIF) degradation, resulting in a pseudo-hypoxic state implicated in PCC/PGL development. Recently, somatic post-zygotic mutations in EPAS1 (HIF2A) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
114
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 149 publications
(125 citation statements)
references
References 37 publications
8
114
0
3
Order By: Relevance
“…The EPAS1 gene was found to be somatically mutated in PPGLs and in patients who had an association between these tumours and polycythaemia and/or, rarely, duodenal somatostatinomas 19,[75][76][77] . Further studies have demonstrated that these mutations can be mosaic, and are occasionally detected in non-tumorous tissue at a low frequency 78 .…”
Section: Box 1 | Features Unique To Ppglsmentioning
confidence: 99%
“…The EPAS1 gene was found to be somatically mutated in PPGLs and in patients who had an association between these tumours and polycythaemia and/or, rarely, duodenal somatostatinomas 19,[75][76][77] . Further studies have demonstrated that these mutations can be mosaic, and are occasionally detected in non-tumorous tissue at a low frequency 78 .…”
Section: Box 1 | Features Unique To Ppglsmentioning
confidence: 99%
“…The recently recognized polycytemia and PGL syndrome was shown to occur as a result gain of function mutations in EPAS1 that resulted in a pseudohypoxic state through reduction in HIF2a degradation mediated by disturbed VHL binding (43,70,71,72). The mode of inheritance for the polycytemia and PGL syndrome (OMIM 603349) is currently unknown due to near exclusive presentation in mosaicism.…”
Section: Polycytemia and Pgl Syndromementioning
confidence: 99%
“…Four patients presented with pheochromocytomas and paragangliomas associated with polycythemia. 9,10 In the present case, after surgery, the patient had a persistent although much lower elevation of plasma norepinephrine (904-1055 pg/mL). Therefore, he should be screened for the presence of somatostatinomas and pheochromocytomas, as well as residual and recurrent paragangliomas.…”
Section: Discussionmentioning
confidence: 40%